Progression on the Roles and Mechanisms of Tumor-Infiltrating T Lymphocytes in Patients With Hepatocellular Carcinoma - Zheng, Xiaoqin; Jin, Wenjie; Wang, Shanshan; Ding, Huiguo (Frontiers in Immunology, 2021)
Liver cancer is one of the most common malignancies, which ranked the fourth in mortality rate. In addition, the morbidity rate of liver cancer is increasing year by year. At present, liver transplantation, tumor resection, and molecular-targeted agents are the primary therapies of HCC. Overall, the survival rate of HCC is low, and the recurrence rate is high. Recent studies found that tumor-infiltrating T lymphocytes (TILs) played essential roles in the development, prognosis, and immunotherapy of HCC. As the central constituent cells of TILs, T cells were also proved to show antitumor and protumor effects for HCC. Foxp3+, CD8+, CD3+, and CD4+ T lymphocytes are the most common subgroups of TILs. This article reviews the roles and mechanisms of different tumor-infiltrating T lymphocyte subtypes in the progression of HCC.